2010
DOI: 10.1155/2010/674908
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Purification, and Partial Characterization ofBacillus subtilisUrate Oxidase Expressed inEscherichia coli

Abstract: Urate oxidase (EC 1.7.3.3) is an enzyme involved in purine metabolism which is used in the treatment of gout and as diagnostic reagent for detection of uric acid. In order to produce this enzyme in large quantities for biotechnological purposes, the gene coding for the Bacillus subtilis urate oxidase was cloned and heterologously expressed in Escherichia coli. Time course induction in E. coli showed an induced protein with an apparent molecular mass of ∼60 kDa. Soluble recombinant enzyme was purified in a sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 29 publications
(31 reference statements)
1
17
0
1
Order By: Relevance
“…These results suggest that PEGylation could mitigate the changes in secondary structure, a finding confirmed by the results of the present study. Kinetic studies on native and PEGylated uricase provide compelling evidence that a wrapping effect occurs by showing significantly decreased Km values in PEGylated uricase, confirming a previous work that also reported that the Km value for uricase had decreased from 5.4 × 10 −5 m to 2.7 × 10 −5 m after modifying with mPEG of 5 kDa [31] …”
Section: Discussionsupporting
confidence: 84%
“…These results suggest that PEGylation could mitigate the changes in secondary structure, a finding confirmed by the results of the present study. Kinetic studies on native and PEGylated uricase provide compelling evidence that a wrapping effect occurs by showing significantly decreased Km values in PEGylated uricase, confirming a previous work that also reported that the Km value for uricase had decreased from 5.4 × 10 −5 m to 2.7 × 10 −5 m after modifying with mPEG of 5 kDa [31] …”
Section: Discussionsupporting
confidence: 84%
“…Partially purified endogenous Auoxp showed optimum activity at pH 8.0 and 40 ° C which are properties shared with urate oxidases from Aspergillus flavus [Li et al, 2006], Bacillus subtilis [Pfrimer et al, 2010] and Candida utilis [Liu et al, 2011]. However, Auox6hp showed an increase in pH optimum to pH 9.5.…”
Section: Discussionmentioning
confidence: 96%
“…Nevertheless, the activity decreases by nearly 50% in 36 h after incubation at 37 °C (Liu et al 2011). The retained activity of uricase from B. subtilis is ~ 50% after incubation at 37 °C for 12 h (Pfrimer et al 2010). Only 15% of uricase activity from A. flavus is preserved after 10-min incubation at 40 °C (Imani and Shahmohamadnejad 2017).…”
Section: The Optimal Temperature and Temperature Stability Of The Tagmentioning
confidence: 99%
“…Furthermore, uricase with a 4-aminoantipyrine peroxidase system is extensively employed as a reagent in the clinical analysis of uric acid in serum (Liu et al 1994). So far, many uricases from various microbes, including Candida utilis (Koyama et al 1996), Bacillus subtilis (Pfrimer et al 2010), Aspergillus flavus (Legoux et al 1992), and Pseudomonas aeruginosa (Shaaban et al 2015), have been recombinantly expressed. Rasburicase mentioned above is the recombinant uricase cloned from A. flavus and expressed in Saccharomyces cerevisiae (Pui et al 2001).…”
Section: Introductionmentioning
confidence: 99%